2010
DOI: 10.3989/gya.122609
|View full text |Cite
|
Sign up to set email alerts
|

Partial chemical composition and antimicrobial activity of <i>Daucus crinitus</i> Desf. extracts

Abstract: The chemical composition of fatty acids and the unsaponifiable fraction of the roots, leaves and stems from Daucus crinitus Desf. were, determined using gas chromatography (GC) and gas chromatography-Mass Spectrometry (GC-MS). The fatty acid fractions of different organs (leaves, stems and roots) were characterized by lauric acid (17.9, 17.5 and 18.1 % respectively) and other long chain fatty acids (until C22). Qualitative and quantitative differences were reported between the unsaponifiable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 14 publications
2
6
0
Order By: Relevance
“…The GLC of fatty acid methyl esters revealed the presence of saturated fatty acids (35%) and unsaturated fatty acids (65%), among which plasmatic and linolenic acid are the main compounds, respectively. These data were in accordance with those reported by Dib et al [7] collected during April was found to contain a mixture of 33 compounds, accounting for 99.01% of the total who they studied the composition of fatty acids in D. crinitus and found that the major fatty acids are lauric acid and behenic acid.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The GLC of fatty acid methyl esters revealed the presence of saturated fatty acids (35%) and unsaturated fatty acids (65%), among which plasmatic and linolenic acid are the main compounds, respectively. These data were in accordance with those reported by Dib et al [7] collected during April was found to contain a mixture of 33 compounds, accounting for 99.01% of the total who they studied the composition of fatty acids in D. crinitus and found that the major fatty acids are lauric acid and behenic acid.…”
Section: Resultssupporting
confidence: 92%
“…The fatty acid fractions of different organs (leaves, stems, and roots) of Daucus crinitus were characterized as lauric acid (17.9, 17.5, and 18.1%, respectively) and other long-chain fatty acids (until C 22 ) [7]. The plants of Daucus spp.…”
Section: Introductionmentioning
confidence: 99%
“…The diameter of inhibition was measured after 24 h at 37°C for bacteria, after 7 days of incubation at 27°C for the fungi and after 48 h of incubation at 37°C for the yeast. The scale of measurement [ 11 ] was the following (disk diameter included): > 20 mm zone of inhibition is strongly inhibitory; < 20 -12 mm zone of inhibition is moderately/midly inhibitory; < 12 mm is not inhibitory. Gentamicin [3 μg/mL(Sigma-Aldrich)], 5-Fluorocytosine, Ketoconazole [5 mg/mL (Sigma-Aldrich)] and DMSO was used as positive and negative controls, respectively.…”
Section: Determination Of the Antimicrobial Activitymentioning
confidence: 99%
“…It is reported that the genus Daucus was the richest genus of the Apiaceae concerning its essential oil content 5 . The leaves are used in their raw form or in an infusion as depurative and diuretic agents 6 . Some species are used in traditional medicine for the treatment of skin disorders, e.g.…”
Section: Introductionmentioning
confidence: 99%